Poverty Alleviation Programs and Economic Development Evidence from Nigeria - Onyernama, Jude Chidi; Adekunle, Bamidele Joseph; Egwu, Chijioke; Ada, Chioma Obi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This work observes the influence of poverty alleviation programs on economic development evidence from Nigeria. Despite various poverty alleviation programs implemented by various past and present governments in Nigeria,it seems that this menace is still living with us. Therefore, the aim of this paper is to find out theorigin of poverty alleviation programmes in Nigeria, the approaches and strategies that Nigerian government has applied to reduce poverty, the appraisal or outcomes of poverty alleviation programmes and the constraints of the programmes in Nigeria.This study covers the period between 1980– 2015.Analyzing time series dataobtained from secondary sources. The essence of the study is to investigate the significant influenceof various poverty alleviation programmes set up by various governments to reduce poverty level inNigeria. The researcher employed the Ordinary Least Square Technique to measure theincidence of poverty. The analysis was facilitated with the use of E-views analytical package.Findings reveal the existence of overall significant influence of poverty alleviation programmes on economicdevelopment of Nigeria.